An Experimental Study on Vietnamese Learners’ Acquisition of Chinese Aspirated and Unaspirated Plosives and Affricates from a Phonetic Contrastive Perspective: 语音对比视角下越南学生习得汉语塞音与塞擦音中送气和不送气音的实验研究 - Thi Son Nguyen; Phuoc Tam Nguyen (Journal of Chinese Language and Culture Studies, 2026)
This study investigates Vietnamese learners’ acquisition of aspirated and unaspirated sounds in Chinese plosive and affricate consonants through a comparative analysis of the Vietnamese and Chinese consonant systems, supplemented by experimental research. Voice Onset Time (VOT) values were extracted using PRAAT and statistically analyzed with SPSS 27. The results reveal the following major findings: (1) Vietnamese initial consonants exhibit a clear voiced–voiceless distinction but lack an aspiration contrast. (2) The Vietnamese plosives zh [ţ] and ch [c] display slight affricate-like characteristics, which warrant further examination. (3) Although Vietnamese learners possess a conceptual awareness of aspiration, psychological factors often lead them to consciously overemphasize or underemphasize the degree of aspiration. Consequently, their production of Chinese aspirated sounds tends to be either overly exaggerated or insufficiently aspirated. (4) The standard deviations of VOT means among Vietnamese learners are larger than those of native Chinese speakers, indicating greater individual variation and lower overall stability in their production of Chinese plosives and affricates.